Knowledge and awareness of a local community on river terrapins in Sungai Perak, Malaysia - Abdul Rahman, Muhammad Farhan; Abd Manaf, Latifah; Ho Nyuk Onn @ Ariffin, Mariani (Penerbit Universiti Malaysia Terengganu, 2019)
Malaysia is the largest and final bastion of wild river terrapins (Bataguraffinis), especially in Sungai Perak in the state of Perak. However, the lack of knowledge among the local communities about the reptiles may accelerate the decline of its population. To overcome the problem, community-based conservation is a valuable tool to educate and carry out sustainable conservation programs. In this study, the knowledge and awareness of a local community in Mukim Bota, Perak, were accessed using a questionnaire. This study found that members of the local community in Mukim Bota were well aware of the existence of river terrapins in their county, with 56% of 397 respondents replying in the affirmative. A total of 62% of respondents knew that sandbanks were the nesting habitats for river terrapins and 70% noticed that the landings and population were decreasing every year. This study strengthened the theory that a knowledgeable and participative community could produce better outcome in sustaining a terrapin conservation programme.